Praktične izkušnje z načrtovanjem in gradnjo prve trajnostno ovrednotene stavbe v Sloveniji s platinastim DGNB - certifikatom - Ivanšek, Domen (Gradbeni vestnik, 2019)
The article describes a newly built educational and demonstration facility called Knauf Insulation Experience Center (KIEXC). In addition to the very diverse architectural structure of the building envelope and BIM modelling, its particularity is in the fact that it is the first newly built building in Slovenia, which was certified under the sustainable DGNB scheme (the highest platinum certificate was achieved), and the first building in Slovenia with Active House certificate. KIEXC is also one of the first pilot projects for the new sustainable buildings assessment framework called Level (s), developed by the European Commission. The article describes the above mentioned sustainable schemes and Level(s), followed by our practical experiences, results and main findings of this pioneering project.
Keywords: Active house; DGNB; Knauf Insulation Experience Center; Level(s); sustainability certificate; trajnostni certifikat